Exploring the Perception of Earned Value Analysis for the Malaysian Construction Industry - Nur Syamimi, Zulkefli; M., Waris; Khairul Firdaus, Anuar; Khan, Asadullah; Adeleke, A. Q. (Future Academy, 2018)
The management of construction projects are becoming more challenging for civil engineers in the 21st century due to increasingly competitive performance expectations from the project stakeholders. However, among the financial and non-financial performance indicators, time and cost monitoring of construction projects are the critical issues for an effective project management. Due to the limitations in traditional time and cost monitoring practices, Earned Value Analysis (EVA) integrates the work scope, cost and schedule to enable effective project performance measurement and as well as future analysis and forecasting. Therefore, this study has proposed EVA and extends its applications for the Malaysian construction industry. The research is based on a quantitative survey that aims to obtain a perception, understanding, enablers and barriers of EVA practices in Malaysia. Feedbacks of the survey reveals that majority of the respondents are not practicing EVA in their working environment. The study has found that there is a good degree of agreement among the respondents regarding the potential enablers of EVA. The survey has also identified the lack of EVA knowledge, expertise and experience as the most important barriers that inhibit its practices among the professionals. The overall findings of this study support the application of EVA as a standardized project control method for the Malaysian construction industry.